CNS Histoplasmosis as a Gliosarcoma mimicker: The diagnostic dilemma of solitary brain lesions - Suha Abu Khalaf; Paragkumar Patel; Carla R. Caruso; Timothy Parrett; Andres Bran (IDCases, 2022)
Histoplasmosis is usually a benign, self-limited disease with lungs predilection. However, it might manifest as a disseminated disease in immunocompromised individuals. The involvement of the central nervous system (CNS) accounts for about 5–10% of cases with disseminated disease. Isolated histoplasmosis of the CNS is rare, and the literature shows only a few reported cases. By imaging studies, it usually presents as an isolated ring-enhancing lesion. Its spectrum of symptoms ranges from acute severe infection to progressive chronic meningitis, which delays the initial diagnosis, correct work-up and initiation of appropriate therapy. We present a case of a 57-year-old man from the Midwest of the United States who misdiagnosed with Gliosarcoma in 2019, for which he underwent appropriate management for Gliosarcoma. Presented for follow-up after new neurological symptoms; worsening in ring-enhancing brain lesions was found on magnetic resonance image MRI. After a re-examination of surgical pathological cases, histoplasmosis of the CNS was diagnosed. Failure of diagnosis CNS histoplasmosis early can lead to poor outcome and decrease chances of recovery.